2021
DOI: 10.1108/jeas-11-2020-0193
|View full text |Cite
|
Sign up to set email alerts
|

Does bank affiliation affect firm capital structure? Evidence from a financial crisis

Abstract: PurposeThis study aims to assess the determinants of corporate debt with a particular focus on bank-affiliated and non-bank-affiliated firms during the global financial crisis.Design/methodology/approachThe authors analyse the data of 395 listed manufacturing firms from Pakistan with 2,370 firm-year observations. The sample is divided into subsamples, namely bank-affiliated, non-bank-affiliated and stand-alone firms. Fixed and panel effect regression models are applied to determine the during, pre-crisis and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Further, there is a significant impact of corruption on bank stability. According to empirical research findings Asteriua et al, (2020)found that corruption and transparency have a negative effect on bank profitability and bank stability, while Zaman et al, (2021) found consistent evidence that corruption has a positive relationship with the banking profitability of Pakistan and Malaysia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, there is a significant impact of corruption on bank stability. According to empirical research findings Asteriua et al, (2020)found that corruption and transparency have a negative effect on bank profitability and bank stability, while Zaman et al, (2021) found consistent evidence that corruption has a positive relationship with the banking profitability of Pakistan and Malaysia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, according to the study's results, there is a significant impact of BSIZE on bank stability. According to Zaman et al (2021)it is indicated that there was significant impact of Money Laundering on bank profitability and stability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations